Como são julgados os juízes? Uma análise do controle disciplinar do Conselho Nacional de Justiça (2005-2013) - Franco, Ivan Candido da Silva de (2015)
One of the main changes introduced by the Brazilian Judicial Reform (Constitutional Amendment 45/2004) was the creation of the National Council of Justice (CNJ). Among its constitutional powers, the control of magistrates’ duties through Administrative Sanctioning Proceedings was significantly questioned, being subject to concentrated control of constitutionality by the Supreme Court (STF). The composition of the Council was also target of criticism, because a considerable part of its members (6 of 15, representing 40% of the total) is not from the Judiciary - coming from the Prosecution, the Bar of Lawyers, in addition to Jurists appointed by National Congress - non-judges counselors. The Judiciary, historically airtight and corporatist, came to be controlled by a new body, the Council of Justice that included not only judges-counselors among its members. The present work studied the CNJ from these two most controversial points, focusing on the disciplinary control exercised by the body over the Brazilian Judiciary. Councils of Justice, especially in their disciplinary feature, must deal with the existent tension between control (or accountability) and judicial independence. We observed this tension in Brazilian National Council of Justice’s performance throughout its history: through an analysis which involved a period from the installation of the CNJ in 2005 until the end of 2013. From this standpoint, we identified the institutional legitimacy strategies used by CNJ for exercising its disciplinary competencies, we analyzed the legal rules arisen during this period, as well as described the profile of the players who occupied the collegiate chairs as counselors. As a result of this observation, it is important to highlight that the Brazilian National Council of Justice shed light on a historically closed Power, despite still presenting transparency issues. The difficulty of finding data on more sensitive matters (sanctioning administrative procedures) and the lack of information disclosure when requested were influent in the research. On Council’s behavior, we resorted to the variable of professionalism (with special focus on the career of origin) to interpret this process. We expected a Council with two characteristics: corporatist and not very harmonic. The quantitative empirical analysis, which constituted a picture of all sanctioning administrative procedures judged by CNJ by the end of 2013, showed a reverse scenario: a non-corporatist and cohesive collegiate. Even in view of these overall characteristics, we found that there are important differences in the decision making behavior and, when present, the career element is influential.